(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2016)
The ˜Theory of Everything is hypothetical theory of physics that explains and connects all known physical phenomena into one. After study, I have reached to a solution that describes the origin of gravitational force and can be postulated as angular piece of this theory. It erase gravity as one of the fundamental forces of nature unifying it with strong nuclear force.